DEVELOPING SIGNS AND SONGS MATERIALS DEALING WITH THE 2013 CURRICULUM FOR THE SEVENTH GRADE STUDENTS IN MTsN BALANG-BALANG - Mardiana Mardiana; Eka Fitriani (Langkawi: Journal of The Association for Arabic and English, 2016)
This research aimed to develop Signs and Songs Materials based on 2013 curriculum for the Seventh Grade Student at MTsN. BalangBalang, Gowa. It was Research and Development (R&D) applied ADDIE model standing for Analysis, Design, Develop, Implement, and Evaluate. The procedures were; 1) analyzing materials needed by students; 2)designing the blueprint; 3) developing the materials through the syllabus of 2013 Curriculum; 4) implementing the product (try-out product); and 5) evaluating the product. The product was tried out to the seventh grade students at MTsN Balang-balang. Type of data obtained in this study was qualitative. The instruments used in this study were questionnaire and rubrics for teacher and expert. Then, the teacher and expert were involved in order to validate the product. They validated three systematic aspects of the product, namely; the organization of the Materials, English Teaching strategies or method, and the content of the materials. Finally, based on the teacher and expert judgment as well as try-out design result, it was found that the developed materials were applicable to be taught for the Seventh Grade of Junior High School as additional learning and teaching materials which help both students and teachers in learning process based on 2013 Curriculum.Keywords: Developing teaching material, signs and songs, the 2013Curriculum